A review on the simulation of aggregate morphologies in mixture performances based on discrete element method. (3rd July 2023) - Gong, Fangyuan; Deng, Rui; Wang, Qinghua; Bai, Jiawei; Cheng, Xuejiao
Highlights: History of DEM and the development of DEM in China are described. Generation of aggregates based on DEM is divided into modeling and filling. Application of DEM in material property and mixture performance is reviewed. Future development directions of aggregate simulation based on DEM are proposed. Abstract: As one of the primary materials in asphalt mixtures, aggregates' complex morphologies and size directly affect the service performances of pavement, such as the structure stability and force transmission path. Discrete element method (DEM) can be effectively used to analyze the influence of aggregate morphology on mixture performances. In order to explore the generation method of aggregate for DEM and the application scope of DEM, the development of DEM and aggregate generation method is summarized in this paper. The process of aggregate generation is reviewed in two steps: shell construction and the model filling. User-defined and external import methods are reviewed in shell construction. Internal filling method, equal size particle filling and other filling methods are reviewed in model filling section. Various examples and principles for each method are separately summarized in the paper. Lastly, the section of test and application is used to verify the virtual experiments with different aggregates can obtain more material motion phenomena and provide more research data. This paper provides a theoretical and technical benchmark for future numerical simulation in road engineering.